Protest camps - Feigenbaum, Anna; Feigenbaum, Anna; Frenzel, Fabian 1975-; McCurdy, Patrick 1975- (Zed Books, 2013)
Cover -- About the authors -- Title -- Copyright -- Contents -- Illustrations -- Acknowledgements -- Introduction -- The multiple origins of organised camping -- 0.1 Global protest camps prior to 2011 -- What makes a 'protest camp'? -- The link between protest camps and (new) social movements -- Concept soup -- 0.2 The concept soup -- Infrastructural analysis and book structure -- 0.3 The infrastructures of protest camps -- An historical review of selected protest camps -- 0.4 Welcome tents like this one at Occupy Bristol form a central feature of many protest camps.